Chromium propionate increases insulin sensitivity in horses following oral and intravenous carbohydrate administration. (25th March 2020) - Spears, Jerry W; Lloyd, Karen E; Siciliano, Paul; Pratt-Phillips, Shannon; Goertzen, Ellen W; McLeod, Sarah J; Moore, Jennifer; Krafka, Kristi; Hyda, Jill; Rounds, Whitney
Abstract: Forty-eight Quarter Horse geldings (3 to 8 yr of age) were used to determine the effects of dietary chromium (Cr), in the form of Cr propionate (Cr Prop ) on insulin sensitivity. Horses were blocked by age, body condition score, and glucose response to concentrate feeding on day 0 and randomly assigned to treatments. Treatments consisted of 0, 2, 4, or 8 mg Cr/d from Cr Prop. Horses were fed daily a concentrate mix at a rate of 0.2 kg/100 kg body weight (BW ) and grass hay at 1.75 to 2.0 kg/100 kg BW. All horses were fed the control diet for 7 d prior to the initiation of the study. After an overnight fast, blood samples from the jugular vein were obtained at 0, 2, and 4 h after concentrate feeding on days 0 and 28 for the determination of glucose, nonesterified fatty acids, and insulin. A glucose tolerance test (GTT ) was conducted on day 42. Glucose was infused via jugular vein catheters, and blood samples were collected at various times relative to dosing for glucose and insulin determination. Plasma glucose on day 28 was affected ( P < 0.05) by treatment, time, and treatment × time. Horses fed 4 mg Cr/d had lesser ( P < 0.05) plasma glucose concentrations than those in the other treatments at 0 h. At 2 h post-feeding glucose concentrations were greater ( P < 0.05) in horses fed 0 or 8 mg Cr/d than in those given 4 mg Cr. Horses fed 2 mg Cr/d had lesser ( P < 0.05) plasma glucose at 4 h post feeding compared with those fed 0 or 8 mg Cr. Plasma glucose did not differ among horses receiving 2 or 4 mg Cr/d at 2 or 4 h. Serum insulin was affected ( P < 0.05) by treatment, time, and treatment × time. Insulin concentrations were greater ( P < 0.05) in horses fed 0 or 2 mg Cr/d than in those given 4 or 8 mg Cr at 0 h. At 4 h post-feeding insulin concentrations were greater ( P < 0.05) in horses given 0 or 8 mg Cr than in those fed 2 or 4 mg Cr/d. Plasma glucose was affected ( P < 0.05) by treatment and time, but not by treatment × time following the GTT. Mean plasma glucose (across sampling times) concentrations were greater ( P < 0.05) in controls than in horses fed 2 or 4 mg Cr/d. Glucose concentrations following the GTT did not differ among controls and horses given 8 mg Cr/d. Following glucose infusion, serum insulin concentrations were greater ( P < 0.05) in horses fed 2 or 4 mg Cr and tended to be greater in those fed 8 mg Cr/d compared with controls. The results of this study indicate that 2 or 4 mg Cr/d from Cr Prop increased insulin sensitivity in adult horses following oral carbohydrate consumption.